Evaluating Police Uses of Force - Stoughton, Seth W.; Alpert, Geoffrey P.; Noble, Jeffrey J. (Book collections on Project MUSE., 2020)
"'Evaluating Police Uses of Force' is an exploration of police brutality and its consequences"--